Time-dependent post mortem changes in the composition of intestinal bacteria using real-time quantitative PCR - Tuomisto, Sari (BioMed Central, 2013)
Post mortem or even normal changes during life occurring in major gut bacterial populations are not known. We investigated Bacteroides sp., Bifidobacterium sp., Clostridium leptum, Clostridium coccoides, Streptococcus sp., Lactobacillus sp. and Enterobacteriacaea ratios in 7 fecal samples from healthy volunteers and in 61 autopsies rectum and cecum samples and studied the effect of post mortem time using quantitative real-time PCR. Bacterial ratios in stool samples from volunteers and rectum samples from autopsy cases were similar and did not change significantly up to 5 days post mortem. In cecum, significant post mortem time-dependent differences were observed in ratios of Bacteroides sp. (p = 0.014) and Lactobacillus sp. (p = 0.024). Our results showed that ratios of Bacteroides sp., Bifidobacterium sp., Clostridium leptum, Clostridium coccoides, Streptococcus sp., Lactobacillus sp. and Enterobacteriacaea can be investigated in autopsy rectum samples up to 5 days after death.